PRELIMINARY STUDY ON THE SUCCESS-FAILURE BALANCE IN IMPLANT THERAPY - Mihaela Mitrea; Edlibi Al Hage Walid; Razvan Radu Maxim; Mihaela Moscu; Irina Jemnoschi Hreniuc; Marius Constantin Moraru; Razvan Tudor Tepordei; Ovidiu Mihail Stefanescu; Oana Elena Ciurcanu; Norina Consuela Forna; Bogdan Sargu Dumachita; Simona Niculescu; et al. (Romanian Society of Oral Rehabilitation, 2022)
Implant therapy has been shown to be predictible, effective and reliable for the replacement of missing teeth in edentulous and partially edentulous patients. Prosthodontic rehabilitation with dental implants requires accurate implant placement for predictable functional and aesthetic outcomes. Implant dentistry has developed numerous advancements in technology, materials, techniques and concepts ti achieve the desire beneficial clinical results. Clinical evidence has demonstrated long-term (> 10 years) survival rates up to 95%. Despite the high success and survival rates of dental implants, failures can and do occur. There are certain factors such as smoking, history of periodontal disease which have been associated with higher rates of implant failure. Futhmore, implant site characteristics such as decreased quantity and or quality of bone, infected sited sites and anatomic localisation such as the posterior maxilla have also been corelated to decreased implant survival.